The Right to Reparation for Victims of Sexual Abuse from a Human Rights Perspective - I Made Wahyu Chandra Satriana; Pranata, Komang Adi (Judge : Jurnal Hukum, 2024)
The regulation of the right to reparation of victims in the crime of sexual abuse reviewed from Law Number 26 of 2000 concerning the Human Rights Court is a regulation in providing reparation (recovery) to victims. Reparation is carried out concerning the physical condition of the victim, the psyche, property, or the rights/social political status of the victim that have been damaged or seized. The form of reparation does not have to be in the form of material/financial compensation, it can also be in other forms, such as a statement of apology from the government. The method in this research is normative legal research. The technique of collecting legal materials is in the form of literature studies through libraries, books and journals related to the Regulation of the right to reparation of victims in the crime of sexual abuse. The regulation of the right to reparation of victims in the crime of sexual abuse reviewed from Law Number 26 of 2000 concerning the Human Rights Court is a regulation in providing reparation (recovery) to victims. Reparations according to Law Number 26 of 2000, Article 35 paragraph (1) states that every victim of serious human rights violations and/or their heirs can receive compensation, restitution and rehabilitation as well as legal protection for victim reparations.